Economic growth and stock market development - Sanchez, Aurora (The Philippine Review of Business and Economics, 1989)
The paper examines Japan's equity capital market to find out whether stock market development proceeds from, or precedes, economic growth. It first starts with a general description of the capital market, its principal players and the various methods of financing investment. It then explores the relationship of economic growth and capital market development, focusing on the Japanese experience. The empirical evidence illustrates the case of growth first before stock market development, a finding which could probe useful for developing countries planning to develop their capital markets.